Amelogenin Peptide-Chitosan Hydrogel for Biomimetic Enamel Regrowth - Mukherjee, Kaushik; Chakraborty, Amrita; Sandhu, Garima; Naim, Sohaib; Bauza Nowotny, E.; Moradian-Oldak, Janet (Frontiers in Dental Medicine, 2021)
We designed synthetic peptides that have demonstrated an effective remineralization potential to restore incipient enamel decay. In order to develop a clinically viable approach we incorporated the amelogenin-derived peptides P26 and P32 into chitosan hydrogel and examined their efficacy in the remineralization of enamel. Peptides in chitosan exhibited increased stability in vitro as compared to peptides in solution at room temperature and at 37°C. Tooth models for enamel erosion (sections) and white spot lesions (blocks) were subject to periods of demineralization. Treatment groups were subjected to remineralization in artificial saliva in the presence of P26 and P32 in solution and in chitosan hydrogel (P26-CS and P32-CS). Quantitative light-induced fluorescence (QLF) was employed to analyze mineral density following demineralization and remineralization across all the treatment groups. Scanning electron microscopy and nanoindentation were used to characterize the surface structure and mechanical strength of regrown enamel. Control enamel sections treated in artificial saliva demonstrated randomly distributed, tiny, needle-shaped crystals with a low packing density and porosities displaying mineralization defects. In samples treated with P26-CS or P32-CS a denser coating of organized hydroxyapatite (HAP) crystals was formed covering the entire surfaces of demineralized enamel window. The hardness and modulus of enamel surfaces were increased after treatment with P26-CS and P32-CS with no significant difference in the mechanical properties between the two peptide hydrogels. Analysis of mineral density by QLF showed that in enamel sections P26 peptide alone or P26-CS significantly enhanced the remineralization. In enamel blocks P26 in solution had a better efficacy than P26-CS.